Gay Acquaintanceship and Attitudes toward Homosexuality: A Conservative Test. (September 2018) - DellaPosta, Daniel
Does acquaintanceship with gays and lesbians produce more accepting attitudes toward homosexuality and gay rights? Although most scholars and laypeople would likely answer in the affirmative, previous work has struggled to answer this question because of the difficulty in disentangling social influence from social selection. Using panel data from the 2006 to 2010 editions of the General Social Survey, this study provides a conservative test of the contact hypothesis for gay acceptance. People who had at least one gay or lesbian acquaintance at baseline exhibited larger attitude changes at two- and four-year follow-ups with regard to support for same-sex marriage and moral acceptance of homosexuality. Furthermore, this contact effect extended even, and perhaps especially, to people who otherwise displayed more negative prior attitudes and lower propensities for gay and lesbian acquaintanceship.